Factors associated with teenage pregnancies Factors associated with teenage pregnancies - Herath, H.M..R.P (My University, 2007)
Data collected with protested interviewer administered questioner. There were 3995 pregnant mothers delivered during the study period in professorial Obstetrics and gynecology unit of which 190 (rate 4.7 percent) were teenage mothers. Data of 186 of subjects were analyzed. The mean age was 17.6 years with a range between 14 and 19 years. Majority of them ( 96.8 percent) were married. Among these teenage mothers 55.4 percent had only primary education or less. The percentage of mothers taken folic acid during first trimester was higher in the 16 years to 19 years group compared to less than 16 group, through the difference was not significant.